'Making Work Pay' in a Rationed Labour Market: The Mini-Job Reform in Germany - Olivier Bargain; Marco Caliendo; Peter Haan; Kristian Orsini (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
To tackle mass unemployment and increase participation rates, the German government over recent years has mainly focused on supply side strategies, including 'making work pay' policies. The 2003 Mini-Job reform introduced an extended subsidy of social security contributions for low wage workers. In this paper, we evaluate the employment effects of this reform using a behavioural tax-benefit microsimulation model. Ex-ante micro policy evaluations based on labour supply models usually ignore involuntary unemployment. This leads to biased estimates of labour supply elasticities and erroneous predictions of the effects of the measure. This aspect is all the more important in a country like Germany, characterized by high unemployment. In this analysis we evaluate the employment effects of the Mini-Job reform by controlling for involuntary unemployment through a double-hurdle model. When focusing on the main labour force, we show that the Mini-Job reform has only a small positive effect on the extensive margin, which is outweighed by a reduction of working hours at the intensive margin.
Keywords: J22; H31; C25; C52; 330; Tax-benefit Systems; Microsimulation; Household Labour Supply; Multinomial Logit; Involuntary Unemployment